(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The main factors affecting the physical and mechanical properties of concrete are density and porosity, that is, the relationship between their volume and the properties of the components of the material. The main technical characteristics of the material, such as its strength and resistance to various conditions, depend on them. The water resistance of materials can be increased by increasing the density and strength of the materials by injecting solutions (cementation, silicate, bituminous, rubberizing, injection of polymer materials), as well as by treating the surfaces of materials with organosilicon polymer materials or by hydrophobizing and fluting.